1996
DOI: 10.1002/hep.510240421
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Hepatic Cholesterol 7α–Hydroxylase Reduces Plasma Cholesterol Concentrations in Normocholesterolemic and Hypercholesterolemic Rabbits

Abstract: plasma cholesterol levels in NZW rabbits. HypercholesThe effect of bile acid depletion and replacement with terolemia in WHHL rabbits was related to the combinaglycodeoxycholic acid on plasma cholesterol concentration of dysfunctional LDL receptors and inhibited tions, hepatic low-density lipoprotein (LDL) receptor cholesterol 7a-hydroxylase. Plasma cholesterol concenbinding and messenger RNA (mRNA) levels, and hepatic trations were reduced significantly when cholesterol 7a-activities and mRNA levels for 3-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The present study demonstrates that direct augmentation of hepatic 7␣-hydroxylase by gene transfer markedly lowers plasma LDL concentrations even in the absence of LDL receptors. These experimental results are consistent with recent studies showing that interruption of the enterohepatic circulation by ileal bypass or complete biliary diversion significantly lowers plasma LDL cholesterol concentrations in WHHL rabbits lacking functional LDL receptors (34,35). Together, these observations indicate that major reductions in LDL concentrations can be achieved through mechanisms independent of LDL receptor induction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study demonstrates that direct augmentation of hepatic 7␣-hydroxylase by gene transfer markedly lowers plasma LDL concentrations even in the absence of LDL receptors. These experimental results are consistent with recent studies showing that interruption of the enterohepatic circulation by ileal bypass or complete biliary diversion significantly lowers plasma LDL cholesterol concentrations in WHHL rabbits lacking functional LDL receptors (34,35). Together, these observations indicate that major reductions in LDL concentrations can be achieved through mechanisms independent of LDL receptor induction.…”
Section: Discussionsupporting
confidence: 92%
“…This study suggests that the modest hypocholesterolemic effect of currently available bile salt sequestrants is related to the limited capacity of these agents to interfere with bile salt absorption and thereby increase hepatic 7␣-hydroxylase activity and bile salt synthesis. More impressive malabsorption of bile salts can be achieved with ileal bypass or complete biliary diversion, and when these procedures are performed in WHHL rabbits, plasma cholesterol concentrations fall by ϳ40% (34,35). However, marked depletion of the enterohepatic bile salt pool is associated with a number of undesirable side effects that make these procedures less than ideal as therapy for clinical hypercholesterolemia (12,40).…”
Section: Fig 7 Effect Of Cholate or Cholestyramine On Hepatic 7␣-hymentioning
confidence: 99%
“…2), although a modest reduction in WT CA-fed mice was observed (Supplementary Fig. 2), which may be downstream of CYP7A1 repression 27 .
Figure 3Cholestasis-induced hepatic dyslipidaemia is attenuated in TRPC5 KO mice. WT and TRPC5 KO mice were fed control (RM3) or CA (0.5% cholic acid supplemented RM3 diet) for 21 days, and ( a ) liver triglyceride (TG), total cholesterol ( b ), and LDL/VLDL ( c ) concentrations were measured.
…”
Section: Resultsmentioning
confidence: 94%
“…Sterol 27-hydroxylase activity and mRNA levels are decreased by bile acids in the rat [156] but unaffected in the rabbit [157,158] and mouse [159]. Cholesterol is reported to increase sterol 27-hydroxylase levels in the rabbit [157] but not in the rat [156] or mouse [159]. It has been reported that there is a coordinate regulation of sterol 27-hydroxylase (CYP27A1) and cholesterol 7α-hydroxylase (CYP7A1) by bile acids in rats [160][161][162].…”
Section: Regulationmentioning
confidence: 99%
“…Bile acids and cholesterol appear, however, to affect this enzyme differently in different species. Sterol 27-hydroxylase activity and mRNA levels are decreased by bile acids in the rat [156] but unaffected in the rabbit [157,158] and mouse [159]. Cholesterol is reported to increase sterol 27-hydroxylase levels in the rabbit [157] but not in the rat [156] or mouse [159].…”
Section: Regulationmentioning
confidence: 99%